Divergent antibody-enhanced entry across SARS-CoV-2 lineages drives variant-specific immunopathology through epistatically constrained spike evolution​​ - Han, Yuru; Xue, Song; Xu, Wei; Zhang, Yuanzhe; Peng, Xiaofang; Zhou, Yunjiao; Wu, Fei; Xie, Minxiang; Wu, Wei; Xia, Anqi; Gao, Yidan; Wu, Jianbo; et al. (LangTaoSha Preprint Server, 2025)
Antibody-dependent enhancement (ADE) of viral entry remains a mechanistically unresolved phenomenon in SARS-CoV-2 variants, with its variant-specificity and pathological consequences poorly defined. Through systematic profiling of 114 monoclonal antibodies (mAbs) across major variants of concern (VOCs), we discover that the Delta variant exhibits uniquely potent ADE mediated by mAbs targeting specific spike (S) epitopes. Crucially, ​​integrative single-cell RNA sequencing of Delta-infected patients provides direct in vivo evidence of ADE-associated immunopathology, revealing significant depletion of FcγR⁺ and C1qR⁺ immune cells (particularly CD16⁺ monocytes and dendritic cells) alongside pan-cellular cytokine hyperactivation, patterns that are absent in wildtype or Omicron infections. Functional dissection demonstrates epistatic interactions among Delta-specific S mutations (L452R, P681R, and D950N), wherein individual mutations enhance ADE in wildtype background but suppress it in Delta context. Longitudinal surveillance reveals fluctuating ADE patterns across variants, with BA.5 sub-lineage exhibiting L452R-mediated resurgence of enhancement. This study establishes ​​variant-specific ADE as an in vivo driver of immunopathology governed by epistatic constraints​​, necessitating continuous risk assessment in evolving variants.
Keywords: SARS-CoV-2; ADE; antibody; variant